Cardiac arrest secondary to type 2 Kounis syndrome resulting from urticaria and angioedema. Issue 7 (14th May 2010) - Connor, Suzy; Child, Nick; Burdon-Jones, David; Connor, Andrew
Abstract : A 43-year-old man with no cardiac history presented with chest pain followed by cardiac arrest. He was successfully defibrillated and underwent primary percutaneous coronary angioplasty to a culprit coronary artery lesion. He later re-presented with a diffuse urticarial rash and lip swelling, reporting that these symptoms had been present for 4 weeks before his cardiac arrest and voicing concern that a further cardiac arrest may be imminent. A diagnosis of post-viral or idiopathic autoimmune urticaria and angioedema was made. Given the absence of cardiac symptoms before the development of the rash, it was hypothesised that coronary artery spasm precipitated by histamine release due to his dermatological condition contributed to his myocardial infarction and cardiac arrest. The final diagnosis was therefore cardiac arrest secondary to type II Kounis syndrome, resulting from idiopathic autoimmune or post-viral urticaria and angioedema.